Host cell heparan sulfate glycosaminoglycans are ligands for OspF‐related proteins of the Lyme disease spirochete. (13th May 2015) - Lin, Yi‐Pin; Bhowmick, Rudra; Coburn, Jenifer; Leong, John M.
Summary B orrelia burgdorferi, the agent of Lyme disease, spreads from the site of the tick bite to tissues such as heart, joints and the nervous tissues. Host glycosaminoglycans, highly modified repeating disaccharides that are present on cell surfaces and in extracellular matrix, are common targets of microbial pathogens during tissue colonization. While several dermatan sulfate‐binding B. burgdorferi adhesins have been identified, B. burgdorferi adhesins documented to promote spirochetal binding to heparan sulfate have not yet been identified. OspEF‐related proteins (Erps), a large family of plasmid‐encoded surface lipoproteins that are produced in the mammalian host, can be divided into the OspF‐related, OspEF‐leader peptide (Elp) and OspE‐related subfamilies. We show here that a member of the OspF‐related subfamily, ErpG, binds to heparan sulfate and when produced on the surface of an otherwise non‐adherent B. burgdorferi strain, ErpG promotes heparan sulfate‐mediated bacterial attachment to the glial but not the endothelial, synovial or respiratory epithelial cells. Six other OspF‐related proteins were capable of binding heparan sulfate, whereas representative OspE‐related and Elp proteins lacked this activity. These results indicate that OspF‐related proteins are heparan sulfate‐binding adhesins, at least one of which promotes bacterial attachment to glial cells.